Percentage of progressors in imaging: can we ignore regressors? - Sofia Ramiro; Robert Landewé; Désirée van der Heijde; Maxime Dougados; Alexandre Sepriano (RMD Open)
Stopping or preventing structural progression is a goal common to all inflammatory rheumatic diseases. Imaging may capture structural progression across diseases, but is susceptible to measurement error. Progression can be analysed as a continuous change score over time (eg, mean change of the van der Heijde-modified Sharp score) or as a binary change score (eg, percentage of progressors according to the modified New York criteria). Here, we argue that the former takes measurement error into account while the latter ignores it, which may lead to spurious conclusions. We will argue that assumptions underlying commonly used binary definitions of progression are false and we propose a method that incorporates (inevitable) measurement error.